A Low Cost Electrosurgery Unit (ESU) Design with Monopolar and Bipolar Methods - Irianto, Bambang Guruh; Wakidi, Levana Forra; Endarta, Ade Ryan; Adam, Madeha Ishag; Aamir, Hafsa (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Surgery using a conventional scalpel causes the patient to lose a lot of blood; this needs to be avoided. The purpose of this research is to make a replacement for the conventional scalpel using a device that utilizes high frequency with a duty cycle setting that is centered at one point. The design of the device is equipped with monopolar and bipolar pulse selection with an increased frequency at 400 kHz, where the duty cycle of bipolar mode can be set to 100% on and the coagulation duty cycle is 6% on and 94% off. The power output of the module was tested using an ESU Analyzer, while cutting the bipolar forceps used soap and meat media. The power inverter circuit was set with the module impedance values ​​of 300Ω, 400Ω, and 500Ω. Power settings were set at high, medium, and low with 2 pulse cutting and coagulation modes. The average power resulted in the lowest power of 32.3Watt and the highest power cutting mode of 58.3Watt. Meanwhile, in the coagulation mode of the lowest power of 3Watt and the highest power of 3Watt, the impedance setting is 500Ω. The module can output power linearly according to settings and can cut media well. Furthermore, the development of making Electrosurgery design in this study is expected to facilitate the surgical process during the surgical procedures.